They murdered "Tiqui": the banalization and fascination of death in drug dealing scenarios - Chacón Echeverría, Laura (2019)
The narration of a murder is the reason of the current article and raises a series of questions about dying in territories governed by drug dealing. Using the deconstruction of ethnographies and narratives, we address three ways of making experience about death in a specific territory, the Community of Metropolis 3. Thus, we think the banalization, the fascination and the governmentalization as dynamics resulting from the homicide that serves as a scene, understanding them as a result of a neoliberal contemporaneity. Because of the latter, there is a need to think of an exit in reconstruction of a social bond worn out by the violence that crosses the community.